Hums Tax Analysis in Islamic Jurisprudence - Niyazov, Ahmed (Scholarya Demo Journal of Ruby, 2019)
Islamic law (jurisprudence) is based on extensive sources. These sources are primarily the Holy Quran, the Sunnah of the Prophet, the community (consensus on evidence) and the reason /qiyas (analogy). On the other hand, the doctrines of Islamic scholars (Ijtihad) are also considered an important source of this law. These teachings, which represent different approaches to religious dogma, have played a special role in the formation of various denominations. A different approach to ayahs and hadiths as well as different interpretations of them from legal aspects, led to the formation of religious law on the basis of a greater number of denominations. One of these teachings is the judgement of Islamic scholars about Hums (fifth part). The expression “one fifth of the captured” 41st verse of Surah al-Anfal was interpreted differently by scholars and led to two different types of beliefs on this subject. This, in turn, led to various forms of religious interpretations and the emergence of different views and trends regarding Hums in fiqh literature. We believe that, since an analytical study of the problem at the doctrine level contributes to scholarly research, it will also be useful in a comparative study of religious denominations.